THE DARK SIDE OF SCHOOL LIFE: AN ANALYSIS OF ELEMENTARY SCHOOL STUDENT BEHAVIOR THAT THREATENS THE LEARNING ENVIRONMENT - Raya Amanda Nur Islami; Yeni Yuniarti (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
Deviant behavior in elementary schools such as bullying, harassment, and verbal or physical aggression reflects a moral crisis and weak social control within the learning environment. This study employs a Systematic Literature Review (SLR) with a qualitative approach to analyze forms of deviant student behavior that threaten the school climate, identify their causal factors, and formulate effective prevention strategies. Thematic analysis of national and international studies reveals that such behavior is influenced by internal factors, including low emotional intelligence, empathy, and learning motivation, as well as external factors, such as authoritarian parenting, negative peer environments, and weak school supervision. These behaviors negatively impact academic achievement, psychological well-being, and students’ social adjustment. Effective prevention requires collaboration among schools, families, and communities through social-emotional learning programs, teacher training in behavior management, safe reporting mechanisms, and strict anti-bullying policies. The findings have practical implications for teachers and policymakers in Indonesia to strengthen character education, empathy, and moral reasoning within the curriculum and to promote a safe, inclusive, and supportive school environment.